On Vulnerability: Probing the Ethical Dimensions of Comparative Theology - Moyaert, Marianne (Religions, 2012)
Though the notion of vulnerability regularly pops up in Clooney’s reflections on comparative theology, he does not develop a systematic account of it. What precisely vulnerability is and how it influences interreligious dialog do not receive enough theoretical grounding. In this article I will probe the complexity of this notion and how it plays out in comparative theology. This will not only enable us to grasp the true originality of Clooney’s project, it will also allow us to uncover its deeper ethical dynamics. For, as I will seek to show, at its core, comparative theology is moved by an ethical concern to enable a just relation between the one’s own tradition and the foreign one. It is my intention to unfold the deep moral dynamics of this particular interreligious approach and to conceptualize the ethical conditions for interreligious learning as present in comparative theology.